Multilevel MPSoC Performance Evaluation: New ISSPT Model - A. Alali; I. Assayad; M. Sadik (Institute of Advanced Engineering and Science, 2015)
To deploy the enormous hardware resources available in Multi Processor Systems-on-Chip (MPSoC) efficiently, rapidly and accurately, methods of Design Space Exploration (DSE) are needed to evaluate the different design alternatives. In this paper, we present a framework that makes fast simulation and performance evaluation of MPSoC possible early in the design flow, thus reducing the time-to-market. In this framework and within the Transaction Level Modeling (TLM) approach, we present a new definition of ISS level by introducing two complementary modeling sublevels ISST and ISSPT. This later, that we illustrate an arbiter modeling approach that allows a high performance MPSoC communication. A round-robin method is chosen because it is simple, minimizes the communication latency and has an accepted speed-up. Two applications are tested and used to validate our platform: Game of life and JPEG Encoder. The performance of the proposed approach has been analyzed in our platform MPSoC based on multi-MicroBlaze. Simulation results show with ISSPT sublevels gives a high simulation speedup factor of up to 32 with a negligible performance estimation error margin.